Multimodal neurophysiological monitoring in healthy infants born at term: normative continuous somatosensory evoked potentials data. (22nd April 2017) - Lori, Silvia; Gabbanini, Simonetta; Bastianelli, Maria; Bertini, Giovanna; Corsini, Iuri; Dani, Carlo
Abstract : Aim: To describe accurate, standardized 1h‐multimodal neurophysiological monitoring (1h‐MNM), while simultaneously recording VEEG, aEEG, and SEP‐C bilaterally from median nerves, and to collect neonatal normative SEP‐C data related to behavioural states. Method: Twenty healthy, term newborn infants (13 males, 7 females; gestational age 37–42wks; mean 39.6wks, standard deviation [SD] 1.3wks) underwent 1h‐MNM within 2 days of life, with focus on recording of the SEP‐C (band‐pass setting 1–100 Hz, rate of stimulation 1.1 Hz, 50 alternate stimuli). Results: 1h‐MNM was easily obtained with identification of cervical (N13) and cortical (N1, P1) SEP‐C responses in all infants. SEP‐C minimal and maximum N1 latencies/N1–P1 amplitudes were identified, bilaterally, during periods of spontaneous sleep active‐quiet‐active (AS‐QS‐AS) and quiet‐wakefulness. Minimal latencies and amplitudes occurred in 60% of active sleep/quiet‐wakefulness, with the maximums in 70% of quiet sleep. The SEP‐C mean values were latencies of N13=13.6ms (SD 1.4ms) and N1=33.6ms (SD 3.9ms) to 34.2ms (SD 4.8ms) in left and right hemisphere respectively; central‐conduction‐time (CCT) (N13–N1), 20.0ms (SD 4.3ms) to 20.6ms (SD 4.8ms); N1–P1 amplitude=4.6ms (SD 2.7ms) to 3.8 μ V (SD 2.2 μ V). Interpretation: 1h‐MNM can record simultaneously VEEG/aEEG/SEP‐C in newborn infants, showing the modulation of SEP cortical responses in relation to behavioural states in all infants studied using an appropriate neonatal method. We emphasize the importance of obtaining neonatal SEP‐C normative data to better identify pathological findings in neonatal brain injury. What this paper adds: Standardized simultaneous recording of video‐ and amplitude‐electroencephalography/continuous somatosensory evoked potentials (SEP) is feasible and safe in neonates born at term. Continuous SEP is always present in all healthy newborn infants in the first 2 days of life. SEP modulation responses could serve as prognostic indicator of brain integrity. This article is commented on by Dachy on page890 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.